2019
DOI: 10.1002/hyp.13400
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate variations as a natural tracer for conduit‐matrix interaction in a complex karst aquifer

Abstract: Large areas of Europe, especially in the Alps, are covered by carbonate rocks, and karst springs are an important source for drinking water supply. Because of their high variability and heterogeneity, understanding the hydrogeological functioning is of particular importance for protection of karst aquifers. In this study, hydrogeochemical investigations characterized the water of a spring draining a complex carbonate‐gypsum karst system in the Alps. The reaction of the spring to a rainfall event was examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Structure of the selected rainfall-discharge reservoir model evolution of the monitored parameters discharge, EC and rainfall are shown as time series in Figure5. The hydrograph reveals distinct increases in response to recharge events with a delay of only a few hours, as also observed by many other studies of karst aquifers (e.g.,Frank et al, 2019;Mudarra & Andreo, 2010;Vigna & Banzato, 2015). The highest discharge values, with up to 2200 L/s, were recorded after major rainfall events in the summer month of2016, 2017 and 2019.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Structure of the selected rainfall-discharge reservoir model evolution of the monitored parameters discharge, EC and rainfall are shown as time series in Figure5. The hydrograph reveals distinct increases in response to recharge events with a delay of only a few hours, as also observed by many other studies of karst aquifers (e.g.,Frank et al, 2019;Mudarra & Andreo, 2010;Vigna & Banzato, 2015). The highest discharge values, with up to 2200 L/s, were recorded after major rainfall events in the summer month of2016, 2017 and 2019.…”
mentioning
confidence: 94%
“…Because springs in this environment are often directly related to precipitation and recharge in the catchment, especially shallow and fast flow karst systems can be investigated by means of tracer tests and hydrograph and chemograph analysis (Hilberg & Kreuzer, 2013). Another important process, which is often described in the literature (e.g., Frank et al, 2019; Martin & Dean, 2001), is the interaction between karst conduits and the surrounding matrix. This process is important, as the matrix can act as a water storage, particularly during dry periods.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Peterson et al [26] showed along the western coast of the Big Island of Hawaii, where groundwater is the only link between land and the ocean and often focused as pointsource discharges [27], that any contamination could affect local coastal ecologies including coral reefs. Frank et al [28] studied a complex gypsum carbonate karst system and showed that the direction of exchange flow changed during high-flow and low-flow conditions by determining the origin and chemical composition of the spring water. They concluded that the direction of the exchange flow is from conduits toward the matrix due to the high contribution of carbonate layers in the spring water during recharge events.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the epikarst plays a significant role in karst recharge and storage (Aquilina et al, 2005;Aquilina et al, 2006;Doctor et al, 2006;Chang et al, 2019). Moreover, lithologic heterogeneity often makes the flow system in karst aquifers complicated (Mocior et al, 2015;Lorette et al, 2018;Frank et al, 2019;Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the multi-approach is expected to help delineate flow paths when the karstic flow system is intricate with lithologic heterogeneity. Besides, spatial studies were rarely conducted for the hydrochemical and isotopic differences of spring water depending on flow types (e.g., low and high discharge), whereas the temporal variation of discharge and hydrochemistry as a function of the hydrological regime was performed by many researchers, including Bicalho et al (2012) Adji et al (2016, Lorette et al (2018), Gil-Márquez et al (2019), Frank et al (2019), and de Filippi et al (2021.…”
Section: Introductionmentioning
confidence: 99%